Institutional Aspects of Forecasting and Organizing Forests Management - APSALYAMOVA, Saida Olegovna; KHACHIR, Bella Olegovna; KHUAZHEV, Oleg Zakireevich; ZYZA, Valeri Pavlovich (Journal of Environmental Management and Tourism; Vol 7 No 2 (2016): JEMT Volume VII, Issue 2(14) Summer 2016, 2016)
This paper considers issues related to the implemented reforms. They show that it is difficult and it takes much time for the forest-based sector to adapt to market relations and international requirements of stable forest management because the forest-based sector has not been of top-priority for the development of economy in the Russian Federation over recent years. It is determined that the basic factor of inefficient forest use was the instability of the legal regulation of forest relations. It led to weak development of institutional forms of forecasting and organizing forests management. It defines basic forms of organizing the forest production, accounting and volume of cuttings of the main forests under the lack of capacities related to deep added-value wood processing in well-forested areas, as well as the increase in the share of soft-wooded broadleaved species and necessity to expand the scope of active restoration of forests, above all the care about young forests. The obtained results show a high level of differentiating the incomes of population, on those with high incomes who can buy wooden products. They mainly live in cities. Incomes of the rural population and people from small provincial towns and settlements, as a rule, do not make it possible to form stable demand for the construction of wooden houses, acquisition of furniture and other products of added-value wood processing. The conducted researches show that the impact of climate and influence of climatic changes on forests can be both positive and negative depending on the country regions. It enables to imagine the impact of climatic changes on the forest-based sector of economy of the Russian Federation. It is proved that the use of the medium growth is not too convenient for estimating the impact of climatic changes on the dynamics of forests. The current growth is better for these purposes, but it is not defined in the contemporary practice of accounting scientific researches when performing forest works. The represented data show that along with this the adaptation of high latitudes landscapes to changes of the climate is difficult in many aspects - ecological, technical, economic, and social. It becomes obvious that the problem of the vast territories of the Russian Federation, many-years’ frozen ground must become the subject of deep scientific researches as well as a component of the international negotiations process related to climatic changes.
Keywords: biodiversity, ecosystem, forest policy, forest services, ' green' economy, habitat, monitoring, recreation